Glibenclamide-Loaded Nanoparticles Reduce NLRP3 Inflammasome Activation and Modulate miR-223-3p/miR-7-1-5p Expression in THP-1 Cells - Roberta Mancuso; Lorenzo Agostino Citterio; Simone Agostini; Ivana Marventano; Francesca La Rosa; Francesca Re; Pierfausto Seneci; Marina Saresella; Mario Clerici (MDPI AG, 2023)
The anti-hyperglycemic drug glibenclamide (Glb) might represent an interesting therapeutic option in human neurodegenerative diseases because of its anti-inflammatory activity and its ability to downregulate activation of the NLRP3 inflammasome. Bi-functionalized liposomes that can cross the blood-brain barrier (BBB) may be used to release Glb into the central nervous system (CNS), overcoming its poor solubility and bioavailability. Here, we analyzed in vitro the effect of Glb-loaded nanovectors (GNVs) and Glb itself on NLRP3 inflammasome activation using a lipopolysaccharide- and nigericine-activated THP-1 cell model. Apoptosis-associated speck-like protein containing a CARD (ASC) aggregation and NLRP3-related cytokine (IL-1β, caspase 1, and IL-18) production and gene expression, as well as the concentration of miR-223-3p and miR-7-1-5p, known to modulate the NLRP3 inflammasome, were evaluated in all conditions. Results showed that both GNVs and Glb reduced significantly ASC-speck oligomerization, transcription and translation of NLRP3, as well as the secretion of caspase 1 and IL-1β (p < 0.05 for all). Unexpectedly, GNVs/Glb significantly suppressed miR-223-3p and upregulated miR-7-1-5p expression (p < 0.01). These preliminary results thus suggest that GNVs, similarly to Glb, are able to dampen NLRP3 inflammasome activation, inflammatory cytokine release, and modulate miR-223-3p/miR-7-1-5p. Although the mechanisms underlying the complex relation among these elements remain to be further investigated, these results can open new roads to the use of GNVs as a novel strategy to reduce inflammasome activation in disease and rehabilitation.